Peran Orang Tua Dalam Mengembangkan Kecerdasan Emotional Intelligence Pada Anak Usia Sekolah Dasar di Yogyakarta - Rahmana, Nur Indah (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2024)
A good education is one that succeeds in developing intelligent individuals intellectually, spiritually, and emotionally. Emotional intelligence is closely related to an individual's psychological condition and mood in the form of certain behaviors. The aim of this study is to determine the development of children's emotional intelligence, the role of parents, and the supporting and inhibiting factors that occur in the development process of the emotional intelligence of students of SD Muhammadiyah Kayen. This study was conducted using qualitative research method and presented with a descriptive method. The main data source was obtained from the interviews with the Principal of SD Muhammadiyah Kayen, Estri Rukmiyanti along with students and students' family of SD Muhamadiyah Kayen. Samples were selected using a non-probability sampling technique. In addition, observation and documentation were also conducted so that this study can categorized as field research. The results of the study are as follows. 1) Children show positive indicators such as having empathy, adaptation, social skills, and emotional control although they still need to improve. 2) Parents play an important role in the running of the program through participation and evaluation in the curriculum planning process and activities in schools.